Best Answer

2x squared minus 5x minus 3 factored is (2x+1)(x-3).

Q: How do you solve 2x squared minus 5x minus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

2x squared - 5x - 3 = (2x +1)(x -3)

6x2 + 5x - 6 is factored out to (2x + 3)(3x - 2).

5x(x - 2)

2x2 - 5x = 3 ∴ 2x2 - 5x - 3 = 0 ∴ 2x2 + x - 6x - 3 = 0 ∴ x(2x + 1) - 3(2x + 1) = 0 ∴ (x - 3)(2x + 1) = 0 ∴ x ∈ {-0.5, 3 }

2x2 + 5x + 3 Notice the first term, which can be rewritten as 2x times x. With this in mind, you can write the equation as...(2x + a)(x + b)...where -a and -b are the answers.You know that a times b is equal to 3.With a little trial and error, you will find:2x2 + 5x + 3 = (2x + 3)(x + 1)

Related questions

2x squared - 5x - 3 = (2x +1)(x -3)

The question contains an expression but not an equation. You cannot solve an expression.

-x2+2x

7x2 -4x -5x2 +2x = 2x2 -2x

(4+x) (2x-3)

(2x - 7)(x + 1)

(x - 1)(5x + 7)

5x lolzz 8)

(2x-3)(x-1)

(2x - 1)(x + 3)

After long division, (2x2-5x+5)/(x-2) = 2x-1+3/(x-2).

5x - 2x = 3x